Glaciology and geological signature of the Last Glacial Maximum Antarctic ice sheet - Golledge, Nicholas R.; Levy, Richard H.; McKay, Robert M.; Fogwill, Christopher J.; White, Duanne A.; Graham, Alastair G.C.; Smith, James A.; Hillenbrand, Claus-Dieter; Licht, Kathy J.; Denton, George H.; Ackert, Robert P.; Maas, Sanne M.; et al. (Quaternary science reviews, 2013)
Dynamical changes in contemporary ice sheets account for significant proportions of their current rates of mass loss, but assessing whether or not these processes are a natural part of ice-sheet evolution requires inference from palaeo-glaciological records. However, a robust mechanism for translating sparse geological data into meaningful interpretations of past glacier dynamics at the continental scale is lacking, since geological archives can be ambiguous, and often their chronology is only poorly constrained. To address this, we combine the interpretation of high-resolution Antarctic ice sheet model results with continent-wide geological evidence pertinent to the dynamical configuration of the ice sheet during the last, and possibly preceding, glacial maxima. We first focus on the thermal regime of the ice sheet, its pattern and velocity of flow, variability in likely subglacial erosion and sediment transport, and how these characteristics evolve during glacial transitions. We show that rapid basal sliding was restricted to discrete outlets that eroded and advected sediment toward and across the continental shelf primarily during the early stages of advance and retreat of the ice sheet, highlighting the need to consider time-transgressive behaviour in the interpretation of geological archives. Secondly, we present new modelling that attempts to improve the fit of our numerical model to geologically-based reconstructions in the Ross Sea. By accounting for locally-enhanced ablation in McMurdo Sound, our new simulation achieves a much closer fit to empirically-derived flow patterns than previously. Growth of the modelled Last Glacial Maximum ice sheet takes place primarily by marine ice accretion in the major embayments, as a consequence of cooler ocean temperatures and reduced sub-ice-shelf melting, and at its maximal extent represents a grounded ice volume excess above present of approximately 8.3 m sea-level equivalent. This figure thus provides an upper bound on the possible Antarctic contribution to deglacial meltwater pulses. •We describe the glaciology of a modelled LGM Antarctic ice sheet model.•We compare its likely geological signature to inferences from empirical records.•We show that greatest subglacial erosion coincides with climate transitions.•We argue that geological records integrate time-transgressive ice-sheet behaviour.